2021
DOI: 10.7171/jbt.21-3203-011
|View full text |Cite
|
Sign up to set email alerts
|

Real-time optical analysis of a colorimetric LAMP assay for SARS-CoV-2 in saliva with a handheld instrument improves accuracy compared with endpoint assessment

Abstract: Controlling the course of the Coronavirus Disease 2019 (COVID-19) pandemic will require widespread deployment of consistent and accurate diagnostic testing of the novel Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Ideally, tests should detect a minimum viral load, be minimally invasive, and provide a rapid and simple readout. Current Food and Drug Administration (FDA)-approved RT-qPCR-based standard diagnostic approaches require invasive nasopharyngeal swabs and involve laboratory-based analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In contrast, the device could judge the detection results and present them to the users on smartphones or its indicator panel by the preset threshold in MCU, rather than judging the results by the users themselves, which would avoid the human errors. Although some automated colorimetric detection devices could also achieve the real-time monitoring of INAATs and judging the detection results, even some of which have been proved to have higher sensitivity than electrochemical detection devices, the high expense of the required sophisticated optics might restrict their extension application [ [36] , [37] , [38] ]. Besides SARS-CoV-2 pseudovirus, another pathogen, Escherichia coli O157:H7 was also employed as a target to evaluate the performance of E-INAATs device on the detection of DNA targets.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the device could judge the detection results and present them to the users on smartphones or its indicator panel by the preset threshold in MCU, rather than judging the results by the users themselves, which would avoid the human errors. Although some automated colorimetric detection devices could also achieve the real-time monitoring of INAATs and judging the detection results, even some of which have been proved to have higher sensitivity than electrochemical detection devices, the high expense of the required sophisticated optics might restrict their extension application [ [36] , [37] , [38] ]. Besides SARS-CoV-2 pseudovirus, another pathogen, Escherichia coli O157:H7 was also employed as a target to evaluate the performance of E-INAATs device on the detection of DNA targets.…”
Section: Resultsmentioning
confidence: 99%
“…In all, we present a novel handheld device for the diagnosis of infectious diseases via colorimetric real-time LAMP assay. Only a few examples of similar platforms have been described, which rely either on pH indicators [ 55 , 56 ] or Hydroxynaphtol blue dye [ 56 ], but, to the best of our knowledge, none of them are based on MG. Additionally, those devices do not make use of ready-to-use mixes, thus making them potentially less applicable to POC settings. Moreover, we have demonstrated that the SMART-LAMP is applicable, without a specific optimization, for the detection of a number of different pathogens using a single positivity threshold for all the assays, hence providing straightforward applications for new diagnostics.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding SARS-CoV-2 RNA detection in clinical samples, the platform presented by Papadakis et al [ 56 ] showed a 97% sensitivity and 100% specificity when analyzing a total of 89 samples. On the other hand, Diaz et al [ 55 ] used the commercial BioRanger diagnostic platform modified for colorimetric LAMP for COVID-19 testing in a limited number of simulated samples spiked with either synthetic RNA or inactivated SARS-CoV-2 virus ( n = 20; 10 positives and 10 negatives), correctly detecting the 10 positive samples and 9/10 of the negatives. In both studies, the results obtained were comparable with those yielded by our SMART-LAMP device.…”
Section: Resultsmentioning
confidence: 99%
“…However, a limitation of the Hilab Molecular is the sample number that can be analyzed at a time; only one sample plus the positive, negative, and intern control. Another device, with similar technology and space for eight microtubes, has been described elsewhere [ 26 ].…”
Section: Discussionmentioning
confidence: 99%